2006
DOI: 10.1097/01.aog.0000245448.19446.81
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Intraepithelial Neoplasia in Adolescent Women

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 12 publications
2
21
0
1
Order By: Relevance
“…González has shown that HPV infection five-fold increases the risk of intraepithelial neoplasia [27]. A similar association is shown in other studies [28,29]. The results show that changes in cytology in the form of ASCUS or LSIL are strongly associated with human papillomavirus infection.…”
Section: Discussionsupporting
confidence: 81%
“…González has shown that HPV infection five-fold increases the risk of intraepithelial neoplasia [27]. A similar association is shown in other studies [28,29]. The results show that changes in cytology in the form of ASCUS or LSIL are strongly associated with human papillomavirus infection.…”
Section: Discussionsupporting
confidence: 81%
“…In G1, the first abnormal smear showed ASCUS in 19% (16), LSIL in 76% (64), and HSIL in 4.8% (4). There was loss of follow-up of 20 patients whose initial lesions were similar to the ones in the remaining subgroup (ASCUS 5 20% [4], LSIL 5 75% [15], HSIL 5 5% [1]).…”
Section: Resultsmentioning
confidence: 99%
“…4 Yet another study showed that adolescents with smear results of ASCUS and LSIL have, respectively, 35% and 36% probability of presenting CIN2/3 in the biopsy, a number raised to 50% in cases of cytopathological HSIL. 16 Such findings reiterate that teenagers might have a prevalence of CIN2 similar to that of the adults. 5 In the present study it was observed that 34.3% (12/35) of the patients with persistent LSIL who were submitted to cervical biopsy had a histopathological CIN2.…”
Section: Discussionmentioning
confidence: 96%
“…La corré lation cytohistologique se caracté rise chez l'adolescente par une plus faible valeur pré dictive en faveur des lé sions sé vè res (CIN2+) pour les frottis HSIL. Dans une sé rie portant sur 517 biopsies, cette valeur n'a é té que de 50 % pour les frottis HSIL [44]. Cette valeur pré dictive plus faible en faveur des lé sions sé vè res s'explique à la fois par les particularité s physiologiques dé jà mentionné es et par la fré quence des infections virales.…”
Section: Efficacité Du Dé Pistage Du Cancer Du Col De L'uté Rus Avantunclassified